2018
DOI: 10.1080/17436753.2018.1510820
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of La2Zr2O7 double-layer thermal barrier coatings

Abstract: Thermal properties of La2Zr2O7 double-layer thermal barrier coatings La2Zr2O7 is a promising thermal barrier coating (TBC) material. In this work La2Zr2O7 and 8YSZ layered TBC systems were fabricated. Thermal properties such as thermal conductivity and coefficient of thermal expansion were investigated. Furnace heat treatment and jet engine thermal shock (JETS) tests were also conducted. The thermal conductivities of porous La2Zr2O7 single layer coatings are 0.50~0.66 W/m/ o C at the temperature range from 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Zirconates such as La 2 Zr 2 O 7 (LZ), Gd 2 Zr 2 O 7 (GZ), and Nd 2 Zr 2 O 7 (NZ) have lower conductivity, higher-temperature phase transformations, and resistance to corrosion but are limited by fracture toughness and low thermal expansion coefficients . However, by double layering the zirconate pyrochlore in a traditional YSZ layer, the thermal expansion mismatches are minimized. , In fact, it was found that a DCL topcoat between pyrochlore LZ or NZ with YSZ has superior thermal properties and relieves thermal stresses between the pyrochlore and the bond coat layer. , Wang et al used finite element method analysis to explore the magnitude of thermal residual stresses in YSZ/LZ TBCs. The finite element method simulation predicted that the residual stresses from thermal expansion and shock would be lower for a double-layer YSZ/LZ than for a single-layer TBC.…”
Section: Design Of Thermal Barrier Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zirconates such as La 2 Zr 2 O 7 (LZ), Gd 2 Zr 2 O 7 (GZ), and Nd 2 Zr 2 O 7 (NZ) have lower conductivity, higher-temperature phase transformations, and resistance to corrosion but are limited by fracture toughness and low thermal expansion coefficients . However, by double layering the zirconate pyrochlore in a traditional YSZ layer, the thermal expansion mismatches are minimized. , In fact, it was found that a DCL topcoat between pyrochlore LZ or NZ with YSZ has superior thermal properties and relieves thermal stresses between the pyrochlore and the bond coat layer. , Wang et al used finite element method analysis to explore the magnitude of thermal residual stresses in YSZ/LZ TBCs. The finite element method simulation predicted that the residual stresses from thermal expansion and shock would be lower for a double-layer YSZ/LZ than for a single-layer TBC.…”
Section: Design Of Thermal Barrier Coatingsmentioning
confidence: 99%
“…42 However, by double layering the zirconate pyrochlore in a traditional YSZ layer, the thermal expansion mismatches are minimized. 43,44 In fact, it was found that a DCL topcoat between pyrochlore LZ or NZ with YSZ has superior thermal properties and relieves thermal stresses between the pyrochlore and the bond coat layer. 43,45 Wang et al 46 used finite element method analysis to explore the magnitude of thermal residual stresses in YSZ/LZ TBCs.…”
Section: Design Of Thermal Barrier Coatingsmentioning
confidence: 99%
“…The (331) peak at 2θ ≈ 36° is absent, so the synthesized La 2 Ce 2 O 7 appears to have the disordered cubic fluorite structure, rather than the pyrochlore structure, although the two are very closely related and the distinction between the two is controversial. [48][49][50][51][52][53][54][55][56][57][58] Microstructural features were observed with a scanning electron microscope (Quanta, FEI). Figure 6A-C shows the microstructure of sintered La 2 Ce 2 O 7 in oxygen at 1600, 1650, and 1700°C for 5 h and Figure 6D-F 7D), but not those HIPed at 1400°C (Figure 7E).…”
Section: Optical Propert Y Predictionmentioning
confidence: 99%
“…However, due to its low coefficient of thermal expansion, high thermal stresses occur near the interface between the top and bond coats, causing delamination and low durability in cyclic thermal environments. Vassen [4,[9][10][11] and our group [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] have developed layered LZ based coatings to mitigate the issue. Double-ceramic-layer (DCL) TBCs have been proposed, which include a top ceramic layer and a thin ceramic buffer layer.…”
Section: Development Of Advanced Tbc Materials For Advanced Gas Turbimentioning
confidence: 99%